PEMBINAAN KARIER PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAERAH (BKD) PROVINSI SULAWESI TENGAH - Roswin, Roswin (Katalogis, 2017)
This study aims to determine whether the monitoring conducted by the Regional Inspectorate of Central Sulawesi Province has run well/effectively or not. This research is a case study with a qualitative approach. The determinations of research location and key informants were done purposively. The data collected were analyzed in stages based on the information from the informants obtained through observations, interviews and documentations. The results show that of the three indicators used to measure the monitoring effectiveness at the Regional Inspectorate of Central Sulawesi Province using H. Emerson theory: Achievement to Monitoring Goals, Achievement to Monitoring Targets, and Timeliness of Monitoring, two indicators: Achievement to Monitoring Targets and Timeliness of Monitoring, were not yet effective. While factor Achievement to Monitoring Goals had already been running well or effectively because the Regional Inspectorate in conducting special monitoring had followed the mechanism and the auditor team had been having understanding about the object to be examined as well as had been using its professionalism in determining the form of content and the intensity of communication so that the object being examined quickly took remedial measures as directed by the auditor team. The results also reveal that the monitoring effectiveness of the Regional Inspectorate of Central Sulawesi Province had not been effective, for some indicators are still experiencing problems therein.